Cost analysis of migraine pharmacotherapy with selective 5HT1 receptor agonists in Ukraine - Yaryna Hrynkiv; Olha Zaliska; Nataliia Maksymovych; Oksana Blavatska (Pensoft Publishers, 2021)
The cost analysis for the relief of migraine attack using selective 5HT1-receptor agonists (frovatriptan, zolmitriptan, risatriptan, sumatriptan) of domestic and imported manufacturers in various dosages and forms of production in the proposed resource online pharmacy chains of Lviv for their efficient and cost effective applications. Among the registered drugs, most dosage forms and trade names are presented for sumatriptan; slightly less for risatriptan and zolmitriptan; for frovatriptan is only one trade name. It has been found that to relieve migraine attack with domestic drugs will be cheaper for patients than imported. Packaging with the same dosage of active ingredient, but with more tablets in the blister is more cost effective for patients. It`s the most economical to stop the migraine attack with Stopmigren (sumatriptan) at a dosage of 50 mg, packing 6 tablets in a blister, and the most valuable drug is Rapimig (zolmitriptan) at a dosage of 50 mg, packing 6 tablets in a blister.